Patent nonnuse: are patent pools as possible solution? - Chavosh, Alireza <1980> (Alma Mater Studiorum - Università di Bologna, 2015)
Studies have depicted that the rate of unused patents comprises a high portion of patents in North America, Europe and Japan. Particularly, studies have identified a considerable share of strategic patents which are left unused due to pure strategic reasons. While such patents might generate strategic rents to their owner, they may have harmful consequences for the society if by blocking alternative solutions that other inventions provide they hamper the possibility of better solutions. Accordingly, the importance of the issue of nonuse is highlighted within the literature on strategic patenting, IPR policy and innovation economics. Moreover, the current literature has emphasized on the role of patent pools in dealing with potential issues such as excessive transaction cost caused by patent thickets and blocking patents. In fact, patent pools have emerged as policy tools facilitating technology commercialization and alleviating patent litigation among rivals holding overlapping IPRs. In this dissertation I provide a critical literature review on strategic patenting, identify present gaps and discuss some future research paths. Moreover, I investigate the drivers of strategic non-use of patents with particular focus on unused strategic play patents. Finally, I examine if participation intensity in patent pools by pool members explains their willingness to use their non-pooled patents. I also investigate which characteristics of the patent pools are associated to the willingness to use non-pooled patents through pool participation. I show that technological uncertainty and technological complexity are two technology environment factors that drive unused play patents. I also show that pool members participating more intensively in patent pools are more likely to be willing to use their non-pooled patents through pool participation. I further depict that pool licensors are more likely to be willing to use their non-pooled patents by participating in pools with higher level of technological complementarity to their own technology.